OBSTACLES AND EFFECTIVENESS OF AUTHENTIC ASSESSMENT IMPLEMENTATION ON GEOGRAPHY SUBJECT - Munandar, Aris; Yani, Ahmad; Ruhimat, Mamat (Indonesia University of Education, 2017)
Authentic assessment is needed to know the development of learners in cognitive, affective and psikomotor. In fact, teachers have difficulty in assessing those three aspects. The aim of this research is to analyze the effectivity and obstacles of the three aspects of the assessment. This research uses descriptive method with 40 participants on Teacher Profession Training Program (PLPG) western Indonesia as respondents. Data tabulation to compare with geography assessment conducted in Europe. The result shows that the effectivity in authentic assessment implementation is low. It caused by the number of student in one class is too high and teacher have a problem in designing assessment rubric.